Impact of Degraded Optics on Monocular and Binocular Vision: Lessons from Recent Advances in Highly-Aberrated Eyes. (17th November 2022) - Devi, Preetirupa; Kumar, Preetam; Marella, Bhagya Lakshmi; Bharadwaj, Shrikant R.
ABSTRACT: Purpose: Optical imperfections of the eye, characterized by higher-order wavefront aberrations, are exaggerated in corneal disease (e.g., keratoconus) and iatrogeny (e.g., keratorefractive surgery for myopia correction, keratoplasty for optical clarity restoration). This article reviews the recent advances on this topic for a comprehensive understanding of how optical degradations in disease models impact retinal image quality and monocular and binocular visual performance. Methods: Published literature over the last decade on retinal image quality and/or monocular and binocular visual functions with corneal irregularity was reviewed based on their relevance to the current topic, study population and strength of study design. The literature was summarized into four themes: 1) wavefront errors and retinal image quality of highly aberrated eyes, 2) monocular and binocular vision loss consequent to degraded optics and visual strategies to optimize performance, 3) impact of optical correction modalities on visual performance and 4) implications for clinical management of patients. Results: Across the 46 articles reviewed, the results clearly indicated that an increase in higher-order aberrations across these conditions had a significant negative impact on the patient's retinal image quality, and monocular and binocular visual functions. Interocular differences in retinal image quality deteriorated visual performance more than an overall worsening of image quality bilaterally. Minimizing optical degradation using rigid contact lenses and adaptive optics technology significantly improves retinal image quality and monocular and binocular vision, but performance remains sub-optimal relative to age-similar healthy controls. Conclusion: Corneal disease and iatrogeny are useful models to understand the impact of optical degradation on retinal image quality and visual performance. Clinical management will greatly benefit from equalizing retinal image quality of both eyes of these patients. Future studies that deepen our understanding of the structure–function relation in these conditions are desirable for advancing vision science in this area and for developing novel clinical management strategies.